Decay resistance of rubberwood (Havea brasiliensis Müll.Arg.) modified with linear chain carboxylic acid anhydrides against basidiomycetes - Hassan, Nuraishah (2018)
The general objective of this study is to improve the basic properties of rubberwood. Rubber trees were cut to the dimensions 100 cm x 14 cm x 25 mm (L x W x T) and kiln-dried (10% to 12% moisture content, MC). The specimens (5 mm x 20 mm x 20 mm) (L x W x T) were prepared, and a Soxhlet extraction with toluene/methanol/acetone (4:1:1 by volume) was performed for 8 h. The specimens were oven-dried (103 °C for 24 h) and cooled (gel silica). Then, vacuum impregnation was conducted, and reactions with acetic, propionic, and butyric anhydrides took place for 0.25 h, 1 h, 4 h, 8 h, 10 h, 15 h, 24 h, 30 h, 36 h, and 48 h at 120 °C. The chemical bonding was confirmed by Fourier transform infrared (FTIR) analysis. The specimens were leached in deionized water and exposed to brown rot (Coniophora puteana) and white rot (Trametes versicolor) in an incubation room at 22 °C for 16 weeks. The reaction of rubber wood with acetic, propionic and butyric anhydrides did not damage its cell walls as shown in SEM images, but the cells shape changed from oval to elliptic. The reaction rate of rubberwood was fastest in ascending order are acetic, propionic and butyric anhydrides. The thickness swelling of rubberwood after submerged for four weeks was not significantly different with anhydrides. However, the propionylated rubberwood at 10.4 WPG gave the lowest thickness swelling. The rubberwood modified with acetic anhydride at 15 WPG gave the lowest decay protection threshold against C. puteana and T.versicolor, than those of propionic and butyric anhydrides. This showed that acetylation gave the best protection to rubberwood against both fungi. The final moisture content had a positive correlation with the weight loss following decay for both C. puteana and T. versicolor. The scanning electron microscope (SEM) images confirmed that the C. puteana and T.versicolor hyphae penetrated the cells in both untreated and modified rubberwood at all levels of WPG.